1999
DOI: 10.1086/514321
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Virology of Ebola Hemorrhagic Fever (EHF): Virus, Virus Antigen, and IgG and IgM Antibody Findings among EHF Patients in Kikwit, Democratic Republic of the Congo, 1995

Abstract: Ebola hemorrhagic fever (EHF) patients treated at Kikwit General Hospital during the 1995 outbreak were tested for viral antigen, IgG and IgM antibody, and infectious virus. Viral antigen could be detected in virtually all patients during the acute phase of illness, while antibody was not always detectable before death. Virus was also isolated from patients during the course of their febrile illness, but attempts to quantify virus in Vero E6 cells by standard plaque assay were often unsuccessful. IgG and IgM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
267
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(283 citation statements)
references
References 5 publications
15
267
0
1
Order By: Relevance
“…The first three subtypes cause severe clinical symptoms in both humans and monkeys, while subtype Reston has caused disease only in monkeys (4,10,11). Ebola virus infection has an acute onset, and frequently, no antibody production is observed at the onset of clinical symptoms (1,7). On the other hand, the virus load in patients' blood and tissues such as liver is extremely high (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first three subtypes cause severe clinical symptoms in both humans and monkeys, while subtype Reston has caused disease only in monkeys (4,10,11). Ebola virus infection has an acute onset, and frequently, no antibody production is observed at the onset of clinical symptoms (1,7). On the other hand, the virus load in patients' blood and tissues such as liver is extremely high (7).…”
mentioning
confidence: 99%
“…Ebola virus infection has an acute onset, and frequently, no antibody production is observed at the onset of clinical symptoms (1,7). On the other hand, the virus load in patients' blood and tissues such as liver is extremely high (7). Therefore, quick and accurate primary screening for Ebola virus infection can be achieved by detection of the viral antigens rather than by detection of specific antibodies (14).…”
mentioning
confidence: 99%
“…Patients who survive usually improve in the second week after onset of the disease, 39 while fatal cases are characterized by more severe early symptoms and signs that progress to multiple organ failure, typically dying in the second week. 59,60 It has been shown that survivors of the infection had an IgM response 2 days after the appearance of symptoms and an IgG response 5 to 8 days after onset of symptoms. On the other hand, in fatal cases there seemed to be a lack of IgG response and only 30% of these patients developed IgM response.…”
Section: Pathophysiology Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…On the other hand, in fatal cases there seemed to be a lack of IgG response and only 30% of these patients developed IgM response. 59,61 therapeutic Measures…”
Section: Pathophysiology Clinical Manifestations and Diagnosismentioning
confidence: 99%
“…Within 6-8 days of fever, hemorrhagic complications can develop, and patients develop increasingly severe symptoms including severe weight loss, delirium, shock, liver failure, massive hemorrhaging, and multi-organ dysfunction. For ZEBOV, clinical signs include elevated liver enzymes, pronounced decreases in peripheral blood lymphocyte counts, especially CD8 T cells, and elevations in inflammatory cytokines [31][32][33][34]. Thrombocytopenia is reported as well as decreases in platelet counts and development of disseminated intravascular coagulation in some but not all fatal cases.…”
Section: Human Diseasementioning
confidence: 99%